Air abrasion before and/or after zirconia sintering: surface characterization, flexural strength, and resin cement bond strength - Abi-rached, Filipe de Oliveira [UNESP]; Martins, Samira Branco [UNESP]; Almeida-júnior, Antonio Alves de; Adabo, Gelson Luis [UNESP]; Góes, Marcio Sousa; Fonseca, Renata Garcia (UNESP) (Operative Dentistry, 2015)
The purpose of this in vitro study was to evaluate the effect of air-abrasion/zirconia sintering order on the yttria partially stabilized tetragonal zirconia polycrystal (Y-TZP) surface characterization (roughness, morphology, and phase transformation), flexural strength (FS), and shear bond strength (SBS) to a resin cement. Y-TZP specimens were air abraded with 50-μm Al2O3 particles after (AS), before (BS), or before and after zirconia sintering (BAS). For roughness (Ra), 30 block specimens (12×12×3.0 mm; n=10) had their surfaces analyzed by a profilometer. Next, on the air-abraded surfaces of these specimens, composite resin discs (n=30) were bonded with RelyX ARC. The bonded specimens were stored for 24 hours in distilled water at 37°C before shear testing. Failure mode was determined with a stereomicroscope (20×). The surface morphology (n=2) was evaluated by SEM (500×). For the four-point flexural strength test (EMIC DL2000), 39 bar-shaped specimens (20×4.0×1.2 mm; n=13) were air abraded according to the three conditions proposed, and an additional group (nonabraded) was evaluated (n=13). The quantitative analysis of phase transformation (n=1) was completed with Rietveld refinement with X-ray diffraction data. Ra (μm) and SBS (MPa) data were analyzed by one-way analysis of variance (ANOVA) and the Tukey test (α=0.05). Pearson correlation analysis was used to determine if there was a correlation between roughness and SBS. For FS (MPa) data, one-way ANOVA and the Dunnett C-test (α=0.05) were used. The air-abrasion/zirconia sintering order influenced significantly (p<0.001) Ra, SBS, and FS. The BS and AS groups presented the highest (1.3 μm) and the lowest (0.7 μm) Ra. The highest SBS (7.0 MPa) was exhibited by the BAS group, followed by the AS group (5.4 MPa) and finally by the BS group (2.6 MPa). All groups presented 100% adhesive failure. A weak correlation (r=−0.45, p<0.05) was found between roughness and SBS. The air-abrasion/zirconia sintering order provided differences in the surface morphology. The nonabraded (926.8 MPa) and BS (816.3 MPa) groups exhibited statistically similar FS values but lower values than the AS (1249.1 MPa) and BAS (1181.4 MPa) groups, with no significant difference between them. The nonabraded, AS, BS, and BAS groups exhibited, respectively, percentages of monoclinic phase of 0.0 wt%, 12.2 wt%, 0.0 wt%, and 8.6 wt%. The rougher surface provided by the air-abrasion before zirconia sintering may have impaired the bonding with the resin cement. The morphological patterns were consistent with the surface roughness. Considering the short-term SBS and FS, the BAS group exhibited the best performance. Air abrasion, regardless of its performance order, provides tetragonal to monoclinic transformation, while sintering tends to zero the monoclinic phase content.
Keywords: Zirconia; Cerâmicas dentárias; Cimentos resinosos; Prótese dentária; Reabilitação oral; Materiais odontológicos